Exploring the Effect of Surface Functionality on the Self‐Assembly of Polyoxopalladate Macroions. Issue 25 (12th May 2015) - Haso, Fadi; Yang, Peng; Gao, Yunyi; Yin, Panchao; Li, Hui; Li, Tao; Kortz, Ulrich; Liu, Tianbo
Abstract The solution behavior of the two polyoxo‐13‐palladates(II) ([PdII13AsV8O34(OH)6]8− and [PdII13(AsVPh)8O32]6−) was studied in detail. We discovered that the countercation‐mediated attraction is the driving force for their self‐assembly into larger architectures. However, the presence of phenyl groups in the periphery of [PdII13(AsVPh)8O32]6− results in an enhanced attraction among these polyanions through hydrophobic interactions, which leads to completely different trends of assembly size for these two very similar clusters when decreasing solvent polarity. An increase of assembly size with increasing solvent polarity was observed for [PdII13(AsVPh)8O32]6−, whereas for [PdII13As V8O34(OH)6]8− it was the opposite, due to the absence of hydrophobic interactions.